Salivary microbial dysbiosis may predict lung adenocarcinoma: A pilot study - Partha Roy; Anupam Sarma; Amal Ch Kataki; Avdhesh Kumar Rai; Indranil Chattopadhyay (Wolters Kluwer Medknow Publications, 2022)
Background: Adenocarcinoma is a more common type of Non-small cell lung cancer (NSCLC). Lung cancer showed a statistically significant increment in the Kamrup Urban district of Assam, Tripura, Sikkim, and Manipur of India. The goal of our pilot study is to identify non-invasive microbial biomarkers to detect lung adenocarcinoma (LAC). Material and Methods: DNA extraction from saliva samples of five LAC patients and five healthy controls was performed by Qiagen DNeasy blood and tissue kit using Lysozyme (3mg/ml) treatment. 16S rRNA genes of distinct regions (V3-V4) were amplified from saliva DNA by PCR. Paired-end sequencing targeting the V3-V4 region of the 16S rRNA gene has been performed on the Illumina MiSeq platform. Raw sequences were analyzed using the QIIME(Quantitative Insights Into Microbial Ecology) software package. Results: Our preliminary results showed that Rothia mucilaginosa, Veillonella dispar, Prevotella melaninogenica, Prevotella pallens, Prevotella copri, Haemophilus parainfluenzae, Neisseria bacilliformis and Aggregatibacter segnis were significantly elevated in saliva of LAC which may serve as potential non-invasive biomarkers for LAC detection. Functional prediction analysis showed that bacterial genes involved in glycosyltransferase, peptidases, amino sugar, and nucleotide sugar metabolism, starch and sucrose metabolism were significantly enriched in LAC. Conclusion: These salivary bacteria may contribute to the development of LAC by increasing expression of glycosyltransferase and peptidases. However to understand their role in pathobiology, studies are required to perform in large cohort.